Implementasi Permendagri Tentang Pedoman Penegasan Batas Daerah dalam Penegasan Batas Daerah antara Kabupaten Karo dengan Kabupaten Dairi - Surbakti, Sriwati Ngena Kenca; Sihombing, Marlon; Warjio, Warjio; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
The purpose of this research is to analyze the implementation of the regulation of Minister of Home Affairs number 141 in the year of 2017 re the affirmation guidelines of territorial borders between Karo Regency and Dairi Regency. This research is conducted in the government of Karo Regency, the government of Dairi Regency and the government of North Sumatera Province. This research applies qualitative method with descriptive approach.Â  Data collection technique is conducted by observing, interviewing, intensive interview, and documenting. This research discovers that the implementation of territorial border regulations between Karo Regency and Dairi Regency has been applied following the regulation of Minister of Home Affairs number 141 in the year of 2017 re the affirmation of territorial boundaries. This is reflected in variable of communication, implementation of conflict management due to territorial borders has been running well enough by direct and indirect communication, although not all of the implementors among the government; variable of resources, implementation of conflict management due to territorial borders are not sufficient related to human resources, budgeting, equipment, information source and authority; variable of disposition, implementation of conflict management due territorial borders have not been applied successfully as a concrete commitment by all level of implementors; variable ofÂ  structural bureaucracy, implementation of conflict management due to territorial borders still have invisible cohesive rhythm and movement among the government of North Sumatera Province with the government of Karo Regency and the government of Dairi Regency.